Characteristics of immunized and un-immunized students, including non-medical exemptions, in Ontario, Canada: 2016–2017 school year. Issue 23 (21st May 2019) - Wilson, Sarah E.; Murray, Jillian; Bunko, Andrean; Johnson, Steven; Buchan, Sarah A.; Crowcroft, Natasha S.; Dubey, Vinita; Loh, Lawrence C.; MacLeod, Melissa; Taylor, Christina; Deeks, Shelley L.
Abstract: Background: Our objectives were: (1) to quantify and describe un-immunized students in Ontario, Canada and assess the extent to which these students have exemptions; and (2) to quantify and describe students with non-medical exemptions (NMEs), including what proportion have up-to-date immunizations. Methods: We examined Ontario students 7 to 17 years-of-age in the 2016–2017 school year using information within a centralized immunization repository. We identified and described students with different immunization/exemption classifications by age, sex, school type, geography and area-level material deprivation using descriptive and multivariable logistic regression analyses. Finally, we assessed the immunization status of students with NMEs, by antigen. Results: We found that students could be recorded as un-immunized with or without an NME, or be immunized with an NME. From a cohort of 1.65 million students, 2.9% of students had zero vaccine doses recorded, and of these 68% had no exemption of any kind. A total of 2.4% of students had an NME. Of these, 39% were un-immunized and 61% had received ≥1 vaccine. Among all students with NMEs, 19–48% had up-to-date immunizations, varying by antigen. Factors associated with increased odds of having a NME and being un-immunized included: attendance at private and 'other' schools, rural residence, and geography. Older age and greater area-level deprivation were associated with a reduced odds. Conclusions: Our assessment revealed that Ontario students with NMEs cannot be assumed to be un-immunized and at risk for all vaccine-preventable diseases. Conversely, not all un-immunized students had NMEs suggesting that future studies of un-immunized children in Ontario must consider additional factors beyond NME status alone. Other jurisdictions that use NME data to inform research and surveillance of vaccine hesitancy and risks for VPD outbreaks may wish to undertake a similar assessment to determine how well student NMEs correlate with student immunization status.